Instrument for hazardous waste transport: Support for sustainability managers of health units (Research, Society and Development, 2021)
The objective of this work was to propose guidelines for sustainability managers who perform their duties within hospital units in Brazil. Assuming a qualitative analysis of the demand for documents and the set of norms common to the national scenario, it was possible to list the procedures in a guide for hospital units. These stablishments are responsible from the generation until the final destination of waste. However, as the transport and destination work is outsourced, this instrument may contribute to the verification and correction of possible non-conformities presented by the service providers. In the activities of collection and external transport of waste from health services, among the risks are the conditioning conditions for the transport, loading and unloading of trucks, risk of a road accident - tipping of the truck, collision, etc. Thus, a series of conditions may be imposed by the environmental agency for the granting of an environmental or operating license for road transport activities of hazardous products or waste. The required documents include, in addition to the company's legal documents, a Certificate of Regularity with IBAMA, a list of vehicles to be licensed and an Emergency Action Plan (PAE).